Teachers’ Practice of Form-Focused Feedback in Writing Classroom Teaching Writing At SMK N 1 Blado, Batang. - Eka Nur Fatmah; Warsono Warsono; Dwi Anggani L.B (English Education Journal, 2022)
This study focused on the description of the teachers’ perception, plan, implementation, and evaluation of Form-Focused Feedback (FFF) in teaching writing. It employed a descriptive qualitative study that applied interviews, questionnaires, and classroom observations in obtaining the research data. The research took place in a vocational high school in Central Java and involved two teachers as well as the twelfth-grade students as the research participants. The results of the study show that the teachers mostly have the same perceptions of Form-Focused Feedback as the experts and researchers of previous related studies. The teachers’ lesson plans show that the teachers included almost all the categories to implement FFF. However, an assessment category which is essential in teaching and learning process was not covered in the lesson plan. The implementation of FFF in teaching writing show that there was only in one out of four meetings the teachers implemented the FFF. Both teachers integrated the FFF and Project Based Learning methods through group discussion. The evaluation of the FFF show that the students made good progress in the form context. It affects the text’s coherence and cohesion and helps students write more accurately. Teachers’ perceptions, planning, and implementation of the FFF have a positive relation to each other. In addition, it suggests that Form-Focused Feedback be used in writing classroom. Also, teachers need to anticipate the facts that the FFF implementation may occur along with the challenges and problems.